PERTUMBUHAN SEMAI GMELINA (Gmelina arborea Roxb.) PADA MEDIA BEKAS TAMBANG SILIKA DENGAN PENAMBAHAN PUPUK KANDANG KAMBING DAN ARANG KAYU Growth for Gmelina (Gmelina arborea Roxb.) on the Post Mine Silica with the Addition of Goat Manure and Wood Charcoal - Basuki Wasis; Novi Anggraini (Jurnal Silvikultur Tropika, 2017)
Mining activity consists of land clearing, erosion of soil horizons, dredging and hoarding. The mining activities will impact to the soil fertility. The addition of soil nutrition can be done by giving goat manure and wood charcoal. This research aims to examine the effect of wood charcoal and goat manure addition to the growth of gmelina (Gmelina arborea Roxb.) seedlings on the post mine silica soil. This research used randomized complete design wit two factorials. Parameter observed in this search is high, diameter and biomass. Observations in 12 weeks whows that single treatment of wood charcoal was not significantly different to all parameters in the 95% interval. The single treatment of goat manure and its interaction with wood charcoal shows a significant different to all parameters observed. The best combination to the growth of gmelina seedling on post mine silica was 100 g of goat manure and 40 gr of wood charcoal.Key words: fertilizer of goat manure, G. arborea, wood charcoal.